Assessment and management of pain/nociception in patients with disorders of consciousness or locked-in syndrome: A narrative review - Bonin, Estelle A. C.; Lejeune, Nicolas; Szymkowicz, Emilie; Bonhomme, Vincent; Martial, Charlotte; Gosseries, Olivia; Laureys, Steven; Thibaut, Aurore (Frontiers in Systems Neuroscience, 2023)
The assessment and management of pain and nociception is very challenging in patients unable to communicate functionally such as patients with disorders of consciousness (DoC) or in Locked-in syndrome (LIS). In a clinical setting, the detection of signs of pain and nociception by the medical staff is therefore essential for the well-being and management of these patients. However, there is still a lot of unknown and a lack of clear guidelines regarding the assessment, management and treatment of pain and nociception in these populations. The purpose of this narrative review is to examine the current knowledge regarding this issue by covering different topics such as: the neurophysiology of pain and nociception (in healthy subjects and patients), the source and impact of nociception and pain in DoC and LIS and, finally, the assessment and treatment of pain and nociception in these populations. In this review we will also give possible research directions that could help to improve the management of this specific population of severely brain damaged patients.